2018
DOI: 10.1371/journal.pone.0191529
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Panicum s. str. (Poaceae, Panicoideae, Paniceae) and insights into its biogeography and evolution

Abstract: Panicum sensu stricto is a genus of grasses (Poaceae) with nearly, according to this study, 163 species distributed worldwide. This genus is included in the subtribe Panicinae together with Louisiella, the latter with 2 species. Panicum and subtribe Panicinae are characterized by including annual or perennial taxa with open and lax panicles, and spikelets with the lower glume reduced; all taxa also share a basic chromosome number of x = 9 and a Kranz leaf blade anatomy typical of the NAD-me subtype photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 77 publications
3
16
1
Order By: Relevance
“…A, S1, S2; Data S6), consistent with a temporal lag between the origin of the group and the diversification of its main lineages. This has been also found in other groups (Dupin et al, ; Zuloaga et al, ; Huang et al, ), although extinct lineages may have dispersed earlier from E Asia as noted above.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A, S1, S2; Data S6), consistent with a temporal lag between the origin of the group and the diversification of its main lineages. This has been also found in other groups (Dupin et al, ; Zuloaga et al, ; Huang et al, ), although extinct lineages may have dispersed earlier from E Asia as noted above.…”
Section: Discussionsupporting
confidence: 75%
“…B; Tables A, S1A). Asymmetric patterns of dispersal between different continents have been previously reported from other groups (e.g., Sanmartín et al, ; Dupin et al, ; Zuloaga et al, ). While animal and plant migration from the Late Miocene (c. 7 Mya) onwards is considered about 30% more frequent from South America to North America (Bacon et al, ), our results inferred 5–7 times as many dispersals in the opposite direction (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the present study, the ML and BI analysis revealed a close relationship between Panicum incomtum, Thyridopepsis xerophila (subtribe Neurachninae), and Dichanthelium acuminatum (subtribe Dichantheliinae, Fig. 3), which was not shown in the study of Zuloaga, Salariato & Scataglini (2018). Therefore, more samples and molecular data of Panicum should be covered to clarify its relationship to other members of tribe Panicinae in further studies.…”
Section: Discussioncontrasting
confidence: 47%
“…3). Zuloaga, Salariato & Scataglini (2018) provided a deeper understanding of the phylogeny of Panicum and suggested a new circumscription of Panicum , including seven sections, based on ndhF data. However, the sample of Panicum incomtum was not included in their data.…”
Section: Discussionmentioning
confidence: 99%